(untitled) (Carte Romanze, 2024)
Commenting If, XIX 13-21 in his Sposizione to Dante’s Commedia (1679), Alfonso Gioia proposed for the detail of the «battezzatori» an interpretation that has so far remained unpublished. The present essay has the twofold aim of placing it in the history of the poem’s exegesis and reflecting on the contribution of the images that the commentator inserted in his notes to relieve Dante of the accusations of obscurity that were frequent during the 17th century.